2016
DOI: 10.1007/s13139-016-0415-z
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella-Mediated Cancer Therapy: Roles and Potential

Abstract: The use of bacteria for cancer therapy, which was proposed many years ago, was not recognized as a potential therapeutic strategy until recently. Technological advances and updated knowledge have enabled the genetic engineering of bacteria for their safe and effective application in the treatment of cancer. The efficacy of radiotherapy depends mainly on tissue oxygen levels, and low oxygen concentrations in necrotic and hypoxic regions are a common cause of treatment failure. In addition, the distribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 75 publications
(91 reference statements)
0
39
0
Order By: Relevance
“…The use of bacteria for the development of immunotherapies for cancer has great potential ( 5 7 ). Particularly, Salmonella is a facultative anaerobe bacteria that can replicate and accumulate in the tumor microenvironment, which offers the potential to amplify the therapeutic effect at the tumor site, avoiding toxicity in surrounding tissues ( 8 10 ). High amount of bacteria are found in necrotic and ischemic regions, which represents an advantage for targeted immunotherapy as these areas are more resistant to radiation and chemotherapy ( 6 , 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of bacteria for the development of immunotherapies for cancer has great potential ( 5 7 ). Particularly, Salmonella is a facultative anaerobe bacteria that can replicate and accumulate in the tumor microenvironment, which offers the potential to amplify the therapeutic effect at the tumor site, avoiding toxicity in surrounding tissues ( 8 10 ). High amount of bacteria are found in necrotic and ischemic regions, which represents an advantage for targeted immunotherapy as these areas are more resistant to radiation and chemotherapy ( 6 , 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Salmonella is a facultative anaerobe bacteria that can replicate and accumulate in the tumor microenvironment, which offers the potential to amplify the therapeutic effect at the tumor site, avoiding toxicity in surrounding tissues ( 8 10 ). High amount of bacteria are found in necrotic and ischemic regions, which represents an advantage for targeted immunotherapy as these areas are more resistant to radiation and chemotherapy ( 6 , 10 12 ). Salmonella efficiency can be seen as the result of a dual effect, a direct tumoricidal activity ( 13 , 14 ) and the result of a strong pro-inflammatory response elicited by the bacteria at the tumor site.…”
Section: Introductionmentioning
confidence: 99%
“…However, all mice infected with KST0650 or KST0651 exhibited 100% survival for more than 9 days. The LD 50 value (LD 50 = 2 × 10 7 cfu) of KST0650 was similar to that of the well-characterized cancer-targeting Salmonella strain KST0651 (LD 50 = 0.4-2 × 10 7 cfu), which suggested that KST0650 had similar or slightly lower virulence than KST0651 (Table S1) [20][21][22]31 . Based on this result, 1 × 10 6 cfu i.p.…”
Section: Resultsmentioning
confidence: 53%
“…The most common bacteria used in this field are the genera Salmonella , Clostridium , Bifidobacterium , Lactobacillus , Escherichia , Pseudomonas , Caulobacter , Listeria , Proteus, and Streptococcus . The use of three species of bacteria, Clostridia , Bifidobacteria , and Salmonellae as vectors for delivering or expressing tumor suppressor genes, anti‐angiogenic genes, suicide genes, or tumor‐associated antigens has been tested in animal models bearing various tumors . Some clinical trials have already been conducted displaying partial responses, and thus further investigation should be performed in humans .…”
Section: Bacteria In Cancer Therapymentioning
confidence: 99%